Is there a role for domestic demand pressure on export performance? - Paulo Soares Esteves; António Rua (European Central Bank (ECB), 2013)
Traditionally, exports behavior is modeled only as a function of the foreign demand and the real exchange rate. However, it is by now widely acknowledged that these variables are not able to fully explain exports developments. This paper suggests considering domestic demand pressure as an additional variable, revisiting its economic rationale and assessing its empirical importance. In particular, we consider the Portuguese case and find that domestic demand developments are relevant for the short-run dynamics of exports. Moreover, it is found that this relationship is asymmetric, being stronger and more significant when domestic demand is falling than when it is increasing.
Keywords: C22; C50; F10; 330; Asymmetry; domestic demand pressure; error correction models; exports